The Evaluation of 2020 Simultaneous Election Logistic Procurement Policy at The Tomohon City General Election Commission - Longdong, Maya Lydia Verawati; Dilapanga, Abdul Rahman; Wawointana, Thelma (Technium Social Sciences Journal, 2023)
The purpose of this research is to find out the results of the evaluation of the logistics procurement policy for the simultaneous elections in 2020 by e-procurement at the General Elections Commission of the City of Tomohon. This study used a qualitative method using data collection techniques in the form of observation, interviews, and documentation. The conclusion of the research results shows that a) The General Election Commission of Tomohon City has procured logistics for the 2020 simultaneous election in accordance with the regulations/provisions issued by the General Election Commission of the Republic of Indonesia where there are 7 types of logistics held through sectoral electronic catalogs where the provider has previously contracted with The KPU of the Republic of Indonesia through a Catalog Contract, so that the Procurement Officers of the Tomohon City KPU purchase logistics from these providers in accordance with the type of logistics offered but in implementing this policy the General Election Commission of Tomohon City has not been effective in preparing planning for the operational costs of logistics procurement without taking into account validation costs and other costs incurred as a result of the addendum to the procurement contract; b) The implementation of the procurement policy through sectoral electronic catalogs has met the logistics needs of the simultaneous election in 2020 but is still not effective and efficient because there are still types of logistics that should be procured through sectoral electronic catalogs but are not held besides this policy absorbs very large operational costs due to expenditures official travel expenses in the context of monitoring and supervising election logistics; c) Obstacles encountered are the provider’s location outside the area making it difficult for communication, increasing security risks, requiring large operational costs, limited human resources and the occurrence of logistics accumulation due to logistics arriving almost simultaneously.